A new facile strategy for higher loading of silver nanoparticles onto silica for efficient catalytic reduction of 4-nitrophenol1. Issue 93 (11th October 2015) - Muthuchamy, N.; Gopalan, A.; Lee, Kwang-Pill
<x xml:space="preserve">Abstract</x> The facile route to higher loading of silver nanoparticles onto a silica support is useful for large-scale synthesis of efficient silver supported catalysts.